Effect of Mesona chinensis polysaccharide on the retrogradation properties of maize and waxy maize starches during storage. (April 2020) - Luo, Yu; Xiao, Yuehuan; Shen, Mingyue; Wen, Huiliang; Ren, Yanming; Yang, Jun; Han, Xiuying; Xie, Jianhua
Abstract: Waxy maize starch (WS) and normal maize starch (NS) were used to investigate the effect of Mesona chinensis polysaccharide (MCP) on the retrogradation properties of maize starch during storage. The rheological properties, water mobility, structural properties and microstructure of samples were investigated. MCP can significantly accelerate the retrogradation of WS and NS, and MCP restricted the water mobility of starch-MCP gels and diminished the decline of the spin relaxation time (T2 ) during retrogradation storage. In addition, the rheological and low field-nuclear magnetic resonance experiments suggested that the retrogradation of WS-MCP system mainly occurred at the later stage of retrogradation (>7 days), while retrogradation mainly took place earlier (<7days) for NS-MCP system. XRD and FT-IR results also suggested that MCP could promote the formation of more ordered structure in starch-MCP gels during storage. Moreover, SEM observation showed that MCP can better maintain the stability of gel structure during aging storage. Graphical abstract: Image 1 Highlights: MCP significantly promoted the retrogradation of WS and NS. MCP limited the migration of water in maize starch-MCP gels. MCP maintains the stability of the maize starch-MCP gels during retrogradation.